Aplikasi Simulasi Monte Carlo dalam Penilaian Risiko Pengurusan Projek untuk Industri Pembinaan - Mat Jusoh, Nurul Salsabila; Zainal, Rozlin; Abd Rahim, Mohd Hilmi Izwan; Shareh Musa, Sharifah Meryam (Research in Management of Technology and Business, 2023)
Nowadays, risk management is important to address as the rapid development of science and technology has resulted in the state of the industrial world and among them is the unpredictable and complex construction industry. Risk management in construction has various limitations that have a significant impact on the overall performance of the project. Monte Carlo simulation is a popular method used in different risk scopes, such as risk assessment and risk modelling. Although this Monte Carlo Simulation method is clearly documented in the standards of the Project Management Institute (PMI), it is not fully used in the real world of the construction industry. Therefore, the objective of this study is to identify the main level of understanding of Monte Carlo Simulation application and identify the main problems of Monte Carlo Simulation application use in risk assessment for construction project management. This research uses a quantitative method through the distribution of questionnaires to the respondents which are 70 G7 contractors (32% feedback) in Johor Bahru. Data analysis is through the use of descriptive statistical methods using the Statistical Package of Social Science (SPSS) software. The study found that the main level of understanding of Monte Carlo Simulation is to measure the potential impact of risk on the project while the main problems with the use of Monte Carlo Simulation is that simulation activities require computer power. In conclusion, this study can help contractors identify the best way that can be applied directly through the problems encountered when using the Monte Carlo Simulation method to assess the risk of large-scale construction projects.